CRISPR-mediated Transfection of Brugia malayi. - Canhui Liu; Alexandra Grote; Elodie Ghedin; Thomas R Unnasch (Public Library of Science (PLoS), 2020)
The application of reverse genetics in the human filarial parasites has lagged due to the difficult biology of these organisms. Recently, we developed a co-culture system that permitted the infective larval stage of Brugia malayi to be transfected and efficiently develop to fecund adults. This was exploited to develop a piggyBac transposon-based toolkit that can be used to produce parasites with transgene sequences stably integrated into the parasite genome. However, the piggyBac system has generally been supplanted by Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) based technology, which allows precise editing of a genome. Here we report adapting the piggyBac mediated transfection system of B. malayi for CRISPR mediated knock-in insertion into the parasite genome. Suitable CRISPR insertion sites were identified in intergenic regions of the B. malayi genome. A dual reporter piggybac vector was modified, replacing the piggyBac inverted terminal repeat regions with sequences flanking the insertion site. B. malayi molting L3 were transfected with a synthetic guide RNA, the modified plasmid and the CAS9 nuclease. The transfected parasites were implanted into gerbils and allowed to develop into adults. Progeny microfilariae were recovered and screened for expression of a secreted luciferase reporter encoded in the plasmid. Approximately 3% of the microfilariae were found to secrete luciferase; all contained the transgenic sequences inserted at the expected location in the parasite genome. Using an adaptor mediated PCR assay, transgenic microfilariae were examined for the presence of off target insertions; no off-target insertions were found. These data demonstrate that CRISPR can be used to modify the genome of B. malayi, opening the way to precisely edit the genome of this important human filarial parasite.